2023
DOI: 10.1021/acsami.2c21202
|View full text |Cite
|
Sign up to set email alerts
|

High Energy Storage Performance of PZO/PTO Multilayers via Interface Engineering

Abstract: Antiferroelectric thin-film capacitors with ultralow remanent polarization and fast discharge speed have attracted extensive attention for energy storage applications. A multilayer heterostructure is considered to be an efficient approach to enhance the breakdown strength and improve the functionality. Here, we report a high-performance multilayer heterostructure (PbZrO3/PbTiO3) n with a maximum recoverable energy storage density of 36.4 J/cm3 due to its high electric breakdown strength (2.9 MV/cm) through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 52 publications
(104 reference statements)
1
4
0
Order By: Relevance
“…The geometric phase analysis mapping (Fig. 3F) confirms the existence of considerable dislocation cores, featured by pronounced shear stress (e xy ) concentration (33), in comparison with the lesser strain fluctuation observed in the BMT-ST film at the same scale (fig. S16, B and C).…”
Section: Structural Mechanismssupporting
confidence: 64%
“…The geometric phase analysis mapping (Fig. 3F) confirms the existence of considerable dislocation cores, featured by pronounced shear stress (e xy ) concentration (33), in comparison with the lesser strain fluctuation observed in the BMT-ST film at the same scale (fig. S16, B and C).…”
Section: Structural Mechanismssupporting
confidence: 64%
“…The lattice spacing of 0.216 nm corresponds to the (012) crystal surface of the NiCo‐LDH, indicating its good crystallinity. [ 35 ] The NiCo‐LDH sample was analyzed using energy‐dispersive X‐ray spectroscopy (EDS) (Figure S3, Supporting Information). The analysis confirmed the presence of Ni, Co, and O in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Cho et al [18] reported a highest negative thermopower of −25 mV K −1 thus far in the poly(2acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS) composite of PEDOT with bisulfate thermodiffusion. Chen et al [19] also achieved a giant negative thermopower of −28.4 mV K −1 through synergistic ion-polymer coordination and Coulomb interactions in the PVA-chitosan aerogel with a polycation electrolyte [poly(diallyldimethylammonium chloride)]/CuCl 2 .…”
Section: Introductionmentioning
confidence: 99%